Research of the head equivalent velocity in the simulation of human-vehicle collision accident. Issue 5 (June 2019) - Zhao, H G; Hao, B Q; Li, C S; Yang, N
Abstract: In this paper, the equivalent velocity of head model based on HIC value is studied. Firstly, based on the existing pedestrian model, a large number of experimental simulation and statistical analysis have been completed after modification, and the functional relationship between HIC value and vehicle pedestrian contact speed has been obtained. Then, a separate head model is established according to the contact characteristics of the original dummy model, and the functional relationship between the HIC value and the collision speed when the head hits the windscreen is obtained by simulation, and the equivalent velocity relationship between the collision speed of the head model and the human-vehicle contact speed is deduced. Finally, according to the existing finite element head model and the coupling calculation method, the simulation results under the coupling calculation condition are explored. The equivalent velocity relation proposed in this paper has guiding significance to the value of collision velocity in the head collision model and also promotes the development of research on human-vehicle collision accidents.